Nietzsche and phenomenology - Rehberg, Andrea (Cambridge Scholars Publishing, 2011)
This collection brings together original essays on a wide variety of topics in the broad area of Nietzsche and phenomenology. Some of these papers take a thematic approach, thinking through key issues that connect or divide Nietzsche and phenomenology.